HUBUNGAN ANTARA MANAJEMEN DIRI DAN PERSEPSI TERHADAP GAYA KEPEMIMPINAN TRANSFORMASIONAL DENGAN MOTIVASI MENGEMBANGKAN KARIR - , SELLY ASTRIANA; , Fathul Himam.Ph.D ([Yogyakarta] : Universitas Gadjah Mada, 2012)
The research is based on the fact that a number of Civil Servants of Indonesia are careless in developing their careers and improving their working potentials. Present research proposes for identify the correlation between selfmanagement and perception over transformational leadership style jointly with career-development motivation on administrator. Proposed hypothesis is: There is positive correlation between self-management and employee perception over transformational leadership style and career-development motivation on employee. Research subject are public servant (PNS) of Surakarta Municipal total 108 subjects. Data was collected by using three equipment, employeeâ selfmanagement perception over transformational leadership style and careerdevelopment motivation questionnaire for employee. Data were analyzed by two predictor regression analysis technique. The result for multiple correlation coefficients were Ry1,2 = 0.748